Application of Fair and Civilized Human Values in the Environment College of Student at Ahmad Dahlan University Yogyakarta - Lisa Retnasari; Suyitno Suyitno; Yayuk Hidayah; Dwi Riyanti (CV. Creative Tugu Pena, 2022)
The purpose of this study was to find out an application of fair and civilized human values in the environment college. The method used case study, with the research subject of students at Pendidikan Guru Sekolah Dasar (PGSD) Ahmad Dahlan University Yogyakarta. In collecting data, the researchers used observation, documentation, and focus group discussions (FGD). The result showed that the implementation of civilized human values in the environment illustrated in the concrete manifestation of social service that can foster a caring attitude towards others, foster high morality, forming Emotional Intelligence (EQ). The implementation of fair and civilized human values in the higher Education environment can be realized by real actions of social service carried out on people who have public problems (starvation). The student in devotion social covers grow high morality, that is feel how is at in other people's position and sensibility social, forming emotional intelligent (EQ) that is intelligence management emotional. Keywords: Environment College, Human Values, Emotional Intelligence